Frantisek Hrubin's Lesanske jeslicky in the light of text sources - Filipi, Michaela (Bohemica Olomucensia, 2013)
The paper deals with Hrubin's last poetry book Lesanske jeslicky. Development of Hrubin's poetry culminates in this book - Hrubin's poetic principles are often being surpassed here and key themes are being completed. This is why Lesanske jeslicky is so important work and why the author reconstructs the proces of writing and analyses text structure of the book.